Snezhnai͡a koroleva - Andersen, H. C. (Hans Christian), 1805-1875 (Shedevry knizhnoĭ illi͡ustrat͡sii - deti͡am, 2011)
This Russian translation of the classic Hans Christian Andersen story shows how the warm human feelings between a boy and a girl overcome the chilling hatred of the evil Snow Queen.